2022
DOI: 10.2196/31758
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Usability of a Clinical Decision Support System: Heuristic Evaluation

Abstract: Background Poor usability is a primary cause of unintended consequences related to the use of electronic health record (EHR) systems, which negatively impacts patient safety. Due to the cost and time needed to carry out iterative evaluations, many EHR components, such as clinical decision support systems (CDSSs), have not undergone rigorous usability testing prior to their deployment in clinical practice. Usability testing in the predeployment phase is crucial to eliminating usability issues and pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In the study of Agharezaei on the examination of the laboratory information system, the highest numbers of problems were related to " exibility and e ciency of use" and the lowest was related to "assisting the user in error detection and recovery" [23] Harrington's study of self-management software for diabetes in 2022 Pareto analysis showed that 29 (57%) of the exploratory violations were related to "system-realworld compliance" and 8 (16%) to "aesthetic and simple design" [26].The results of studies Khajavi [22] and Nabouti[16], the component of " exibility and compatibility of the system" with the highest number of problems has been reported, which is in line with the results of the present study. Other study identi ed the mean severity scores range of exibility and e ciency of use base on heuristic evaluation on Clinical Decision Support System was 0.66, in which scores closer to 0 indicate a more usable system [27]. In the study of Ahmadian [28], the component of system adaptation to the real world and the aesthetic and simple design aspects had the most di culty in evaluating the radiology information system.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Agharezaei on the examination of the laboratory information system, the highest numbers of problems were related to " exibility and e ciency of use" and the lowest was related to "assisting the user in error detection and recovery" [23] Harrington's study of self-management software for diabetes in 2022 Pareto analysis showed that 29 (57%) of the exploratory violations were related to "system-realworld compliance" and 8 (16%) to "aesthetic and simple design" [26].The results of studies Khajavi [22] and Nabouti[16], the component of " exibility and compatibility of the system" with the highest number of problems has been reported, which is in line with the results of the present study. Other study identi ed the mean severity scores range of exibility and e ciency of use base on heuristic evaluation on Clinical Decision Support System was 0.66, in which scores closer to 0 indicate a more usable system [27]. In the study of Ahmadian [28], the component of system adaptation to the real world and the aesthetic and simple design aspects had the most di culty in evaluating the radiology information system.…”
Section: Discussionmentioning
confidence: 99%
“…We will first perform heuristic evaluation 55 of CDS interface usability before testing with clinician participants. This will consist of an expert team of three evaluators with experience in emergency medicine as well as CDS design who will navigate through different aspects of the CDS and judge the compliance and usability of the tool in agitation management triangulated between their expertise and usability standards.…”
Section: Methods and Analysesmentioning
confidence: 99%
“…We anticipate that our final product will be an EHR-integrated web application through a dedicated graphical Application Programming Interface. 54 Phase 2: usability testing of ED-TREAT Heuristic evaluation We will first perform heuristic evaluation 55 of CDS interface usability before testing with clinician participants. This will consist of an expert team of three evaluators with experience in emergency medicine as well as CDS design who will navigate through different aspects of the CDS and judge the compliance and usability of the tool in agitation management triangulated between their expertise and usability standards.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…Usually, such systems are rule-based logical systems developed on pre-defined rules supplied by medical experts [10]. Despite the explainability offered by such systems, there are many challenges such as poor user experience and scarcity of involvement of medical experts in forming the knowledge base [12,20].…”
Section: Visually Interactive Dss In Healthcarementioning
confidence: 99%
“…Examples of data-centric approaches are summarizing individual data instances (using common statistical methods like mean, mode, and variance), visualizing the data distribution to compare feature values of an instance to those across the remaining dataset and observing changes in model predictions through what-if analysis [18,19,22,57]. Additionally, data-centric explanations include data-driven rule-based approaches that are adopted commonly in medical DSS for assisting health experts [4,12,19,27,47].…”
Section: Exploration In Visual Explanationsmentioning
confidence: 99%